Chronic obstructive pulmonary disease in the long-term care setting: current practices, challenges, and unmet needs. (November 2017) - Suarez-Barcelo, Manuel; Micca, Joseph L.; Clackum, Sharon; Ferguson, Gary T.
Abstract : N/A: Chronic obstructive pulmonary disease (COPD) is a prevalent and disabling disorder in the United States, especially affecting older individuals, women, and those with a history of smoking. Studies show that COPD may be underrepresented, underdiagnosed, and undertreated in elderly patients residing in long-term care (LTC) facilities. The quality of care for LTC residents with COPD is heterogeneous in regard to both the facility and the patient. For LTC facilities, care should be driven by staff education, interstaff communication, and interfacility communication. From the perspective of the LTC patient, choice of medication and device should be based on appropriate diagnosis, comorbidities, ability to perform treatment, and patient preferences. Nebulization is currently underutilized in LTC settings, although it would benefit older patients with low peak inspiratory flow, cognitive impairment, and/or physical impairment, which may preclude them from using other inhalation devices. Authors developed a COPD treatment algorithm that focuses on three primary patient aspects to consider when deciding on respiratory device in patients in LTC facilities: inspiratory flow, hand dexterity and coordination, and cognitive capacity.